Respuesta :
Answer:
Option 'b' and 'e' are equivalent.
Step-by-step explanation:
Given : Expression [tex]-\frac{1}{4}x+\frac{3}{4}=12[/tex]
To find : Which equations are equivalent to expression ?
Solution :
a) [tex]-\frac{4x}{1}+\frac{3}{4}=12[/tex]
It is not equivalent.
b) [tex]-\frac{x}{4}+\frac{3}{4}=12[/tex]
It is equivalent.
c) [tex]\frac{x+3}{4}=12[/tex]
It is not equivalent.
d) [tex]\frac{1}{4}(x+3)=12[/tex]
It is not equivalent.
e) [tex]\frac{-x}{4}+\frac{3}{4}=12[/tex]
It is equivalent.
Answers:
B
C
E
Step-by-step explanation:
Answer B, C, and E are equivalent to the original, which are all created by rewriting fractions in a different ways.